Dietland - Walker, Sarai (Boston : Houghton Mifflin Harcourt, 2015)
Plum Kettle does her best not to be noticed, because when youre fat, to be noticed is to be judged. Or mocked. Or worse. With her job answering fan mail for a popular teen girls magazine, she is biding her time until her weight- loss surgery. Only then can her true life as a thin person finally begin. Then, Plum finds herself falling down a rabbit hole and into an underground community of women who live life on their own terms. At the same time, a dangerous guerrilla group called Jennifer begins to terrorize a world that mistreats women, and as Plum grapples with her personal struggles, she becomes entangled in a sinister plot.
Keywords: Obesity -- Surgery -- Fiction; Feminists -- Fiction